2009
DOI: 10.1073/pnas.0909993107
|View full text |Cite|
|
Sign up to set email alerts
|

Onset of frictional slip by domain nucleation in adsorbed monolayers

Abstract: It has been known for centuries that a body in contact with a substrate will start to slide when the lateral force exceeds the static friction force. Yet the microscopic mechanisms ruling the crossover from static to dynamic friction are still the object of active research. Here,we analyze the onset of slip of a xenon (Xe) monolayer sliding on a copper (Cu) substrate. We consider thermal-activated creep under a small external lateral force, and observe that slip proceeds by the nucleation and growth of domains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
43
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 26 publications
3
43
0
Order By: Relevance
“…In the case of perfect commensurability, the huge difference between the static friction force and the weak inertia force provided by the oscillating QCM results in a very high activation barrier (for example, E dep ≃ 10 7 eV has been estimated for a Xe monolayer on the Cu(111) surface in the absence of defects). Such barrier has been found to drop dramatically by decreasing the interfacial commensurability [32]. By combining these results with the experimental findings, the following interpretation of the QCM data is proposed:…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…In the case of perfect commensurability, the huge difference between the static friction force and the weak inertia force provided by the oscillating QCM results in a very high activation barrier (for example, E dep ≃ 10 7 eV has been estimated for a Xe monolayer on the Cu(111) surface in the absence of defects). Such barrier has been found to drop dramatically by decreasing the interfacial commensurability [32]. By combining these results with the experimental findings, the following interpretation of the QCM data is proposed:…”
mentioning
confidence: 65%
“…This structural transition is accompanied by a sharp increase of the interfacial commensurability and static friction [31]. The depinning of a commensurate interface has been shown to be a thermally activated process with an associated barrier E dep ∝ εU 0 (F s − F )/F s F , where F is the applied lateral force and F s the static friction force [32]. In the case of perfect commensurability, the huge difference between the static friction force and the weak inertia force provided by the oscillating QCM results in a very high activation barrier (for example, E dep ≃ 10 7 eV has been estimated for a Xe monolayer on the Cu(111) surface in the absence of defects).…”
mentioning
confidence: 99%
“…1a). In this case a finite and large external force is required to dislodge the slider atoms from the potential minima, so as to nucleate, at finite temperature, 5,6 the onset of sliding.…”
Section: Introductionmentioning
confidence: 99%
“…Reguzzoni et al (1) recognized that atoms in the adsorbed layer do not move in parallel, but that motion is initiated collectively by fractions of the layer, which one may call droplets. Specifically, they suggested that frictional slip occurs by the nucleation of a small commensurate domain that then expands by displacing a domain wall.…”
Section: Nucleation Of a Critical Droplet As The Trigger Of Creepmentioning
confidence: 99%
“…Theorists, however, suffer from another handicap: They cannot apply their beloved tools-such as linear-response theory-to creep phenomena in a straightforward fashion. This is why it is difficult to develop a theory for creep motion, which is precisely what Reguzzoni et al (1) succeeded in doing for a specific system in this issue of PNAS. Their work is impressive because they not only derive the functional relationship between creep motion and external force, but they manage to ascertain the correct material-specific parameters with surprisingly simple and thus elegant analytical calculations.…”
mentioning
confidence: 99%